2020
DOI: 10.3390/w12082222
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Standing Column Well Operation on Carbonate Scaling

Abstract: Standing column well constitutes a recent promising solution to provide heating or cooling and to reduce greenhouse gases emissions in urban areas. Nevertheless, scaling issues can emerge in presence of carbonates and impact their efficiency. Even though a thermo-hydro-geochemical model demonstrated the impact of the water temperature on carbonate concentration, this conclusion has not been yet demonstrated by field investigations. To do so, an experimental ground source heat pump system connected to a standin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Minor depositions were observed twice using an optical flowmeter during routine verification. The first deposition was composed of calcite and was observed in January 2019 (Cerclet et al, 2020). The second deposition was observed in July 2019.…”
Section: Column Bmentioning
confidence: 98%
See 1 more Smart Citation
“…Minor depositions were observed twice using an optical flowmeter during routine verification. The first deposition was composed of calcite and was observed in January 2019 (Cerclet et al, 2020). The second deposition was observed in July 2019.…”
Section: Column Bmentioning
confidence: 98%
“…In open-loop systems, clogging can be observed in underground and aboveground equipment (Gjengedal et al, 2019). Kim et al (2017) identified biological clogging in the underground equipment of an SCW, and Cerclet et al (2020) observed minor calcite scaling on the aboveground equipment. A strategy to understand clogging processes involves carrying out column experiments.…”
Section: Introductionmentioning
confidence: 99%
“…4). See Beaudry et al (2019), Nguyen et al (2020), andCerclet et al (2020) for further details about this installation. Multi-flow rate thermal response test.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…• The geological environment was not favorable: the hydraulic conductivity of the aquifer (K = 5.7 10 -7 m/s) in Varennes is low as well as the thermal conductivity (k = 2.74 W m -1 K -1 ) (Beaudry et al, 2019). Furthermore, the groundwater composition promoted carbonate scaling (Cerclet et al, 2020).…”
Section: Standing Column Wells In Cold Climatesmentioning
confidence: 99%